Acute odontogenic maxillary sinusitis treated endodontically - two case reports and 15-day CBCT outcome - Lauter Eston Pelepenko Teixeira; Marina Canali Lângaro; Mateus Silveira Martins Hartmann (Universidade Estadual de Campinas, 2018)
Patients presented acute recurrences from Otorhinolaryngology treatments with unilateral symptoms compatible with maxillary sinusitis with a dental origin (MSDO). Cone beam computed tomography (CBCT) showed sinus extensive membrane thickening that was not visible at periapical exam associated to the maxillary molar infection in both cases. Respiratory structures assessment was possible using a 6-inches field of view CBCT. Non-surgical endodontic treatment (case 1) performed and retreatment (case 2) showed a fast symptoms relief. Recall examination after 15 days revealed healthy soft tissues with normal periodontal probing and no dental mobility. In addition, 15-day CBCTs revealed initial maxillary sinus membrane recovery after the endodontic approaches in the reported cases. No additional medical intervention nor antibiotics administration were necessary in these MSDO cases management. Long-term follow-up in such cases is advisable to exclude other potential dental or respiratory issues. Diagnose and follow-up using CBCT presented significant sinus membrane thick reduction with no symptom's recurrence after the endodontic treatment.